Demographic drivers of the growth of the number of Aboriginal and Torres Strait Islander people living with dementia, 2016–2051. (22nd August 2022) - Temple, Jeromey; Wilson, Tom; Radford, Kylie; LoGiudice, Dina; Utomo, Ariane; Anstey, Kaarin J.; Eades, Sandra
Abstract: Objective: To examine the demographic drivers that contribute to the future growth in the population of Aboriginal and Torres Strait Islander peoples living with dementia in Australia. Methods: Design: Multistate, Indigenous status, cohort component, population projection model. Setting: National‐level, Aboriginal and Torres Strait Islander population. Data: Data prepared by the Australian Bureau of Statistics on births, deaths, migration and identification change. Australian Institute of Health and Welfare estimates of dementia prevalence alongside estimates from several studies. Major outcome measures: Number of older people living with dementia alongside a decomposition of demographic drivers of growth. Results: By 2051, the relative growth in the number of Aboriginal and Torres Strait Islander peoples aged 50+ with dementia ranges from 4½ to 5½ times (under three prevalence scenarios) its 2016 estimate. Cohort flow (the gradual movement of younger cohorts into the 50+ age group, and the depletion of older cohorts from death, over time) is a key driver of the growth in the number of older people living with dementia. Conclusions: High growth in the number of people living with dementia poses implications for culturally appropriate care, health‐care access and support for Aboriginal and Torres Strait Islander families, carers and their communities.